1996
DOI: 10.1016/s0928-8244(96)00069-7
|View full text |Cite
|
Sign up to set email alerts
|

Phase-variable outer membrane proteins in Escherichia coli

Abstract: Escherichia coli contains at least two phase-variable proteins in its outer membrane. One, termed antigen 43 (Ag43), is the product of the metastable flu gene located at min 43.6 on the E. coli chromosome and is responsible for colony form variation and for autoaggregation in liquid media. Ag43 is composed of two proteinaceous subunits, alpha 43 and beta 43 in 1:1 stoichiometry. alpha 43 (apparent M(r) 60,000) is surface expressed, extends beyond the O-side chains of smooth lipopolysaccharide and is bound to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
83
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(92 citation statements)
references
References 15 publications
(26 reference statements)
8
83
1
Order By: Relevance
“…Most auto-aggregation studies performed thus far have found a uniform distribution of autotransporters such as Ag43 and AIDA-I (Benz & Schmidt, 1992;Henderson et al, 1997b;Owen et al, 1996;Sherlock et al, 2004). However, these studies were mainly done using laboratory E. coli K-12 strains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most auto-aggregation studies performed thus far have found a uniform distribution of autotransporters such as Ag43 and AIDA-I (Benz & Schmidt, 1992;Henderson et al, 1997b;Owen et al, 1996;Sherlock et al, 2004). However, these studies were mainly done using laboratory E. coli K-12 strains.…”
Section: Discussionmentioning
confidence: 99%
“…4A). Most other studies so far have indicated that Ag43 is distributed uniformly on the cell surface (Henderson et al, 1997a;Owen et al, 1996). However, in the majority of these studies, Ag43 was overexpressed.…”
Section: Cellular Location Of Ag43mentioning
confidence: 93%
“…A survey of enteropathogenic and urinary tract infectious strains showed that 77 and 60 %, respectively, of these were capable of Ag43 expression (Owen et al, 1996). Moreover, many strains posses duplex or multiple copies of the gene, as seems to be the case in enteropathogenic and enterohaemorrhagic subtypes Roche et al, 2001;Torres & Kaper, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it is expressed by many pathogenic strains. Thus, a survey of enteropathogenic and urinary tract infection E. coli strains showed that 77 and 60%, respectively, of these strains were capable of Ag43 expression (21). Although E. coli K-12 has only one copy of the flu gene, it appears that the situation for wild-type strains is more complex and that two or more copies are present in enteropathogenic E. coli strains and some enterohemorrhagic E. coli strains (22,28).…”
Section: Discussionmentioning
confidence: 99%